Clinical and surgical correlation of hip MR arthrographic findings in adolescents. Issue 6 (June 2016) - Jawahar, Anugayathri; Vade, Aruna; Lomasney, Laurie; Okur, Gokcan; Evans, Douglas; Subbaiah, Perla
Abstract: Objective: The purpose of this study was to analyze the utility of MRA-H in adolescents by comparing the results of imaging with surgical findings and/or clinical outcome. Material and methods: After obtaining appropriate IRB approval, the Radiologic Information System database was queried for all patients 13–18 years of age who underwent MRA-H from 2004 through 2013. The electronic medical record was reviewed for clinical history, clinical examination findings, and operative notes. MRA-H images were reviewed for soft tissue abnormalities (labral tear, paralabral ganglion, articular cartilage loss, synovitis, ligament tears) and bony abnormalities (cam-type femoroacetabular impingement (FAI), pincer-type FAI, hip dysplasia). MRA-H findings were correlated with surgical findings and with clinical outcomes. Results: Twenty-six patients with labral tears by MRA-H were included in study and grouped as follows: Group I) patients who underwent surgical management (n = 10); group II) patients managed non-surgically (medication, intra-articular injection, physical therapy) (n = 9); group III) patients lost to follow up after being advised to have surgery (n = 7). With regard to presenting symptomatology, 87.5% of patients with labral tear had groin pain. Of those patients who were diagnosed with a labral tear, 52% were categorized as idiopathic labral tears, 26% as secondary tears (secondary to abnormal bony morphology), and 22% as traumatic labral tears. The labral tears were found to be anterior in 61% and posterior in 22%. Associated articular cartilage lesions were found in 29% of patients. In group I (surgical patients), MRA-H labral findings were confirmed at surgery in 9/10. Seventy percent of labral tears in our study had some form of abnormal bony morphology. Nine of the 12 patients with bone abnormalities were derived from group I patients. Six out of 7 patients with cam-type FAI had a labral tear. Conclusion: Labral tears diagnosed by MRA-H in the adolescent population correlated well with clinical examination and surgical findings. Also, MRA-H contributed by defining bony morphology that was directly applied to surgical management. Non-surgical management of labral tears diagnosed on MRA-H had a generally favorable outcome.